MAKNA ETIS DAN ESTETIS TARI ADANINGGAR KELASWARA - Darmasti Darmasti (Institut Seni Indonesia Surakarta, 2013)
Adaninggar Kelaswara dance performance is a creativity that comes from Hikayat Amir Hamzahepisodes Putri China (Princess of China). The fame of Wong Agung Menak affects Adaninggar toserve him to be his queen. Adaninggar does not know that a man may only have four wives incustom of Islam. Wong Agung Menak have already had the fourth wife who was also a soldiernamely Kelaswara. Burned by the feeling of owning Wong Agung, there is a duel betweenAdaninggar and Kelaswara Here, Adaninggar can be killed by Kelaswara caused byviolating Ethical value and Islam that is force something. Big jealousy and boastful resulted thedeath of Adaninggar. The dance of Adaninggar Kelaswara contains high aesthetic value that is acreativity of duel between two beautiful women who ignited blind -love emotion. The Aesthetic ofAdaninggar Kelaswara dance can be observed through ‘maju beksan, beksan and mundur beksan’